EFFECT OF COMPACTION ENERGY ON THE MARSHALL CHARACTERISTICS' OF AN ASPHALT` CONCRETE MIX - Hasoloan Pasaribu, Bosar
EFFECT OF COMPACTION ENERGY ON THE MARSHALL CHARACTERISTICS OF AN ASPHALT CONCRETE MIX, Bosar Hasoloan Pasaribu, 1999, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. ompaction is the process of reducing the air voids content of a bituminous mixture through the use of compaction energy. Compaction causes the particles to pack closely together. n the research described this thesis, the effect of compaction energy on the Marshall characteristics of an asphalt concrete mix was investigated by applying various levels of compaction energy at the optimum bitumen content obtained from 2x75 blows compaction. The compaction energies applied were 35, 50, 75, 100, 200, 300 and 400 blows of the Marshall hammer. At compaction energy levels exceeding 100 blows, the energy was applied by 3 procedures : A, B and C. Specimens were also prepared at optimum bitumen content using the Percentage Refusal Density (PRD) procedure. onsistent tendencies of Marshall characteristics were found when compaction energy increased from 35 to 300 blows. However at 400 blows compaction the tendencies changed; the extraction tests showed that the aggregate grading had changed and was finer than the initial grading. The change in aggregate grading was caused by the fracture of some aggregate particles. The fracture of aggregate particles increased the volume of air voids in the mix resulting in a decrease in density and an increase in VIM and VMA. The fractured aggregates were not coated by bitumen resulting in a decrease in immersed stability and Index of Retained Strength, and an increase in flow thereby reducing the Marshall Quotient of immersed Marshall specimens. t 300 blows compaction, the density of specimens compacted by the three procedures was a maximum and the refusal condition is considered to have been reached at this level of compaction energy. The Marshall characteristics for the three procedures at this level of compaction energy were almost similar i.e. density, VIM, VMA, VFB, stability, flow and Marshall Quotient were about 2.441 g/cc, 2.15 %, 13.80 %, 84.50 %, 1775 kg, 3 mm and 600 kg/mm, respectively. These results were slightly different from PRD test results and this may be due to the difference in compaction method. omparison of the data from Marshall and PRD specimens shows that the PRD test results are comparable at 180, 230 and 245 compaction blows following procedures B, C and A, respectively